Penilaian Tingkat Kematangan Tata Kelola Teknologi Informasi Dengan Menggunakan Domain PO (Plan and Organise) - Sandra Jamu Kuryanti (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
IT governance assessment is carried out with the hope that the maturity level of governance at PT. ASAHIMAS FLAT GLASS TBK Jakarta. The results of the assessment carried out show that every IT process in the PO domain is at level 2, namely at the Define Process stage. Gap analysis in the process generally has a maturity level at level 2, which management expectations are generally at level 4. The maturity index value obtained shows the level of maturity in each process. Furthermore, it is known that 100% of the total 10 IT COBIT domain PO processes are at maturity level 2, while the expectations are 4 so there is a gap in maturity level 2. There is a gap in the 10 control objectives at PT. ASAHIMAS FLAT GLASS TBK Jakarta, which is 10 gaps in the PO domain. The COBIT findings from the 10 gaps that must be adjusted are PO1, PO2, PO3, PO4, PO5, PO6, PO7, PO8, PO9, and PO10.